Alsini Eldery Stick / Baihaqi Aura Putra - Putra, Baihaqi Aura (2022)
The older one gets, the weaker one's physical body is starting from reduced energy, increasing disease, even some elderly people sometimes need assistive devices in carrying out some daily activities. One of the most common activities is walking. This study was made to help the elderly in walking downhill or uphill. Then made a design that can be stored easily. The method used in carrying out this research begins with field observations, identifying the activities of the elderly who will go to the mosque that goes down and uphill, then determine what kind of products are suitable for the problems experienced by the elderly. The results obtained are a walking stick design that is easy to carry, lightweight, safe, and easy to store when performing prayers in the mosque that is adapted to ergonomic principles.